Biometal Dyshomeostasis and Toxic Metal Accumulations in the Development of Alzheimer’s Disease - Li, Yong; Jiao, Qian; Xu, Huamin; Du, Xixun; Shi, Limin; Jia, Fengju; Jiang, Hong (Frontiers in Molecular Neuroscience, 2017)
Biometal dyshomeostasis and toxic metal accumulation are common features in many neurodegenerative disorders, including Alzheimer’s disease (AD), Parkinson’s disease and Huntington’s disease. The neurotoxic effects of metal imbalance are generally associated with reduced enzymatic activities, elevated protein aggregation and oxidative stress in the central nervous system, in which a cascade of events lead to cell death and neurodegeneration. Although the links between biometal imbalance and neurodegenerative disorders remain elusive, a major class of endogenous proteins involved in metal transport has been receiving increasing attention over recent decades. The abnormal expression of these proteins has been linked to biometal imbalance and to the pathogenesis of AD. Here, we present a brief overview of the physiological roles of biometals including iron, zinc, copper, manganese, magnesium and calcium, and provide a detailed description of their transporters and their synergistic involvement in the development of AD. In addition, we also review the published data relating to neurotoxic metals in AD, including aluminum, lead, cadmium and mercury.